Clinical and evolutionary aspects of classification and treatment for pediatric hydrocephalic syndrome: a bibliographic review (Research, Society and Development, 2022)
Introduction: The term hydrocephalus comes from the Greek and means “water in the head”. It is characterized by an increase in the amount and pressure of cerebrospinal fluid or cerebrospinal fluid, leading to dilatation of the ventricles and compression of nervous tissue. Hydrocephalus is not a specific disease. Rather, it represents a diverse group of disorders, which result from impaired circulation and absorption of cerebrospinal fluid (CSF) or, in rare circumstances, increased production by a choroid plexus papilloma. Objective: to review clinical and evolutionary aspects of the classification and treatment for pediatric hydrocephalus syndrome, its clinical presentations and procedures that provide a better resolution of this neurosurgical emergency. Method: a computerized bibliographic search was carried out, using the keywords (Endoscopic third ventriculostomy (ETV); ventriculoperitoneal shunt for hydrocephalus (VP ​​shunt); Treatment and Diagnosis.), in the following databases (SciELO, Google Scholar, Brazilian Journal of Neurosurgery, Arquivos Ciência Saúde, American Journal of Neurosurgery and Publab). Conclusion: there are few references in the Brazilian literature that address the topic on clinical and evolutionary aspects of classification and treatment for pediatric hydrocephalus syndrome. Thus, it is important to encourage research on the subject, enabling the strengthening and expansion of their professional practice in this area, as critical training and the development of skills to assist children with neurological disorders are fundamental.